Active Control of Road Impulse Noise Based on Modified Error-constrained FNxLMS - Zhang, Lijun; Wang, Zifei; Meng, Dejian; Pi, Xiongfei (IEEE International Conference on Information Communication and Signal Processing (Online), 2024)
This paper presents a novel approach to address road noise cancellation in vehicles, focusing on robustness against impulsive noise. While active noise control (ANC) technologies have shown promise in reducing road noise, their effectiveness is often hindered by the presence of impact noise from sources such as speed bumps and damaged road surfaces. To overcome this challenge, we propose an enhanced ANC algorithm combining a reference signal normalization technique with a threshold algorithm. This approach aims to improve the system's robustness by effectively filtering out impact noise while preserving the desired noise reduction in other frequency bands. The methodology involves conducting road tests on surfaces with speed bumps to evaluate the algorithm's performance under real-world conditions. Through comprehensive analysis of noise reduction, we demonstrate the efficacy of the proposed algorithm in cancelling road noise, particularly in the presence of impact events. Our experiments suggest that the algorithm achieves significant improvements in noise reduction without compromising system stability. This work contributes to the advancement of ANC technology in vehicles by addressing a key challenge and providing a practical solution for enhancing passenger comfort and vehicle noise quality. Overall, the proposed approach offers a promising avenue for achieving effective road noise control in automotive applications, paving the way for quieter and more comfortable driving experiences.